1995
DOI: 10.1159/000276756
|View full text |Cite
|
Sign up to set email alerts
|

Major Basic Protein and Topical Administration of Ketotifen in Pollinosis under Natural Allergen Provocation

Abstract: In this study we investigated the potential relation among subjective symptoms, blood eosinophil counts and the levels of major basic protein (MBP) in serum throughout the pre- to postpollen season. In addition, we compared the effects of topical administration of ketotifen on these parameters between the prophylactic treatment group (n = 10) and the postsymptomatic treatment group (n = 10). We found that (1) the levels of MBP in serum during the season were significantly higher than those before the season an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Subjective symptoms identified by questionnaire consisted of nasal blockage, secretion, and sneezing, as described previously (19, 20). The four‐point symptom scale was as follows: 0, no symptoms; 1, mild; 2, moderate; and 3, severe.…”
Section: Methodsmentioning
confidence: 99%
“…Subjective symptoms identified by questionnaire consisted of nasal blockage, secretion, and sneezing, as described previously (19, 20). The four‐point symptom scale was as follows: 0, no symptoms; 1, mild; 2, moderate; and 3, severe.…”
Section: Methodsmentioning
confidence: 99%
“…However, none of these clinical studies have reported on the effect of ketotifen on ECP levels in nasal or lacrymal fluids, although it is well‐recognized that ECP is increased in tears during AC and that ECP is correlated with signs, symptoms, and number of eosinophils in tears. Interestingly, by looking at the effect of ketotifen treatment during the pollen season, Kato et al have reported a decrease in blood eosinophil count, as well as a decrease in serum ECP or MBP, suggesting a possible direct effect of ketotifen on peripheral blood eosinophil activation and degranulation and maybe on tissue eosinophils (50, 51). In another study, Leonardi et al have described that the level of ECP in tears of patients with VKC was decreased after treatment with lodoxamide, another mast cell stabilizer and anti‐allergic drug (52).…”
Section: Discussionmentioning
confidence: 99%
“…After microscopically identifying Japanese cedar pollen grains that were dropped onto glass microscope slides, the number of pollen grains (per cm 2 ) was counted following our previously reported methods. 22,24 Patients with JCP and control subjects in the clinical study…”
Section: Pollen Countsmentioning
confidence: 99%